KONSEP DAN PRINSIP HUKUM JAMINAN PADA PERBANKAN SYARIAH - St. Hadijah Wahid; Wandi Pratama Putra (Al-Aqad, 2024)
The concept of Sharia Guarantee is an important aspect in Islamic economic activities, especially in Islamic banking. Sharia collateral is known as al-rahn in Arabic, which means fixed, continuous, and retained. In the perspective of Islamic law, al-rahn is used as collateral for debt by allowing the repossession of the property if the debtor defaults. In Islamic banking, the concept of collateral is based on Islamic principles, such as taqarrub (approach to God), justice, and balance. The principles of security law generally include certainty, proof of claim, public interest, repayment of debt, compliance, agreement, adherence to higher law, and the principle of justice. These principles form a fundamental framework to protect the interests of creditors, maintain the integrity of transactions, and accommodate relevant ethical and legal values. The method of exploring the principles of Islamic security law is through deduction and induction. Deduction is used to combine the legal principles of sharia contracts with the legal principles of sharia guarantees, while induction is used to develop legal principles by taking specific rules regarding sharia guarantees. The principles of sharia guarantee law concern aspects of freedom, equality, justice, harmony, honesty and writing.